2020
DOI: 10.1007/s00253-020-10599-8
|View full text |Cite
|
Sign up to set email alerts
|

Archaea, specific genetic traits, and development of improved bacterial live biotherapeutic products: another face of next-generation probiotics

Abstract: Trimethylamine (TMA) and its oxide TMAO are important biomolecules involved in disease-associated processes in humans (e.g., trimethylaminuria and cardiovascular diseases). TMAO in plasma (pTMAO) stems from intestinal TMA, which is formed from various components of the diet in a complex interplay between diet, gut microbiota, and the human host. Most approaches to prevent the occurrence of such deleterious molecules focus on actions to interfere with gut microbiota metabolism to limit the synthesis of TMA. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 97 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…Therefore, the prevention of these diseases could rely on the supplementation of TMA-consuming Methanomassiliicoccales (so-called 'archaebiotics' 14 ). As a proof-ofconcept, a single inoculation of M. luminyensis B10 (the so-far unique isolate of Methanomassiliicoccales 150 ) significantly lowered the concentration of plasma TMAO in standard C57BL/6 laboratory mice through a 30days experiment, despite a very poor colonization 151,152 . M. smithii and two TMA-using methanogenic archaea (non-human and environmental) also showed a protective effect on a mouse model prone to atherosclerosis 151 .…”
Section: Archaea In Human Health and Diseasementioning
confidence: 99%
“…Therefore, the prevention of these diseases could rely on the supplementation of TMA-consuming Methanomassiliicoccales (so-called 'archaebiotics' 14 ). As a proof-ofconcept, a single inoculation of M. luminyensis B10 (the so-far unique isolate of Methanomassiliicoccales 150 ) significantly lowered the concentration of plasma TMAO in standard C57BL/6 laboratory mice through a 30days experiment, despite a very poor colonization 151,152 . M. smithii and two TMA-using methanogenic archaea (non-human and environmental) also showed a protective effect on a mouse model prone to atherosclerosis 151 .…”
Section: Archaea In Human Health and Diseasementioning
confidence: 99%
“…It is worth noting that some bacteria from the phylum Proteobacteria may also be able to metabolize the TMAO ingested via the diet into TMA via TMAO reductase using metabolic retroconversion [ 54 ]. Finally, it has recently been found that intestinal archaea such as some members of the order Methanomassiliicoccales are able to reduce TMAO to methane [ 55 ]. Therefore, a current area of research relies on the use of such microorganisms as potential probiotics, in order to reduce the circulating levels of TMAO, which have been associated with an increased cardiovascular disease risk.…”
Section: The Impact Of Gut Microbiota On Choline Metabolismmentioning
confidence: 99%
“…However, the delivery systems designed for this purpose face many challenges such as early release of bacteria while passing through the stomach and the small intestine, which may reduce viability of bacteria that are sensitive to the conditions in the upper part of the digestive tract . Research into next-generation probiotics is focused on putative applications on a number of alternative microorganisms, many of which are more vulnerable to the environment of the upper gastrointestinal (GI) tract and can benefit from direct delivery to the colon. …”
Section: Introductionmentioning
confidence: 99%